ANALISIS PENERIMAAN PENGGUNA APLIKASI DANA MENGGUNAKAN METODE TECHNOLOGY ACCEPTENCE MODEL - Thejakusuma, Alvin Pratama; Yunus, Arfan; Renny (KHARISMA Tech, 2024)
Dana Application is a technology-based financial application that enables users to perform various financial transactions. The purpose of this research is to analyze the acceptance of the Dana application by users using the Technology Acceptance Model (TAM) method. This research is conducted based on existing issues, and the objective is to analyze the user acceptance of the Dana application using the Technology Acceptance Model (TAM) approach. This allows for the identification of service aspects that need improvement and maintaining the performance of the Dana application based on user satisfaction levels. Subsequently, the research findings indicate that all hypotheses are valid, thus concluding that the Dana application is well-received by the public.